2016
DOI: 10.18632/oncotarget.7950
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hepatitis B virus envelope proteins induce endoplasmic reticulum stress: involvement of cannabinoid axis in liver cancer cells

Abstract: HBV represents the most common chronic viral infection and major cause of hepatocellular carcinoma (HCC), although its exact role in liver tumorigenesis is unclear. Massive storage of the small (SHBs), middle (MHBs) and large surface (LHBs) HBV envelope proteins leads to cell stress and sustained inflammatory responses. Cannabinoid (CB) system is involved in the pathogenesis of liver diseases, stimulating acute and chronic inflammation, liver damage and fibrogenesis; it triggers endoplasmic reticulum (ER) stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…DEPs participated in protein processing in the ER, consistent with the results of previous studies [45,46], which revealed facilitation of viral replication by ER alternations and activation of the unfolded protein response with viral infections. Interestingly, all of the 10 proteins were upregulated, including the heat shock proteins 71 kDa, 105 kDa (hsph1), and hsp90-alpha and beta-1(S1 File).…”
Section: Discussionsupporting
confidence: 91%
“…DEPs participated in protein processing in the ER, consistent with the results of previous studies [45,46], which revealed facilitation of viral replication by ER alternations and activation of the unfolded protein response with viral infections. Interestingly, all of the 10 proteins were upregulated, including the heat shock proteins 71 kDa, 105 kDa (hsph1), and hsp90-alpha and beta-1(S1 File).…”
Section: Discussionsupporting
confidence: 91%
“…The liver is an important organ for the synthesis of proteins and lipids, so hepatocyte ER has appropriate adaptive capacity [31]. When the liver is in a state of inflammation for a long time, ER stress is maintained at a high level, which leads to hepatic dysfunction and progression of liver diseases, even HCC [32].…”
Section: Discussionmentioning
confidence: 99%
“…We selected the median as the group cut-off for survival plots. Upper aerodigestive track (32) Large intestine (60) Pleura (11) Oesophagus (27) Biliary tract 9Autonomic ganglion 17Cervix 2 BioMed Research International for statistical analyses. We select the median expression level for splitting the high-expression and low-expression cohorts.…”
Section: Immunohistochemical (Ihc) Detection Of Tissuementioning
confidence: 99%
“…ER reside on many molecular chaperones that assist protein folding and assembly 34 . Numerous studies show that viral infections can alter endoplasmic reticulum (ER) and activate the unfolded-protein response (UPR), thereby facilitating viral replication [35][36][37][38] . In the current study, 21 of the differentially expressed proteins were involved in protein processing in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%